2019
DOI: 10.1002/ece3.5471
|View full text |Cite
|
Sign up to set email alerts
|

Pheromone‐binding proteins based phylogenetics and phylogeography of Maruca spp. from Asia, Africa, Oceania, and South America

Abstract: Variations in the functional response of legume pod borer (Maruca vitrata) populations to sex pheromone blends were observed in Asia and Africa. Hence, this study was carried out to understand the differences in pheromone‐binding proteins (PBPs) among Maruca populations in Asia, Africa, Oceania, and South America. A de novo transcriptome assembly was adopted to sequence the entire transcribed mRNAs in M. vitrata from Taiwan. The raw‐sequence data were assembled using homologous genes from related organisms in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…A previous study on two M. vitrata Chinese populations suggested sex polymorphism between these populations, since the sex pheromone from the Huazhou population was composed of (E)-10-hexadecenal, (E, E)-10, 12-hexadecadienal, and (E, E)-10,12-hexadecadienol in the ratio of 10.3:100:0.7, whereas the sex pheromone of the Wuhan population presented a different ratio of 79.5:100:12.1 [ 38 ]. In line with this finding, a recent study confirmed the presence of different Maruca species and/or subspecies in different continents [ 34 ] and differential production of sex pheromone compounds in different geographical locations [ 38 , 39 ], which is possible due to the presence of polymorphism in M. vitrata with respect to the pheromone production. With no doubt, the high pheromone polymorphism recorded in M. vitrata across diverse geographic areas in Africa, India, and Asia limits the potential use of the traps when used as monitoring or mass trapping tools.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…A previous study on two M. vitrata Chinese populations suggested sex polymorphism between these populations, since the sex pheromone from the Huazhou population was composed of (E)-10-hexadecenal, (E, E)-10, 12-hexadecadienal, and (E, E)-10,12-hexadecadienol in the ratio of 10.3:100:0.7, whereas the sex pheromone of the Wuhan population presented a different ratio of 79.5:100:12.1 [ 38 ]. In line with this finding, a recent study confirmed the presence of different Maruca species and/or subspecies in different continents [ 34 ] and differential production of sex pheromone compounds in different geographical locations [ 38 , 39 ], which is possible due to the presence of polymorphism in M. vitrata with respect to the pheromone production. With no doubt, the high pheromone polymorphism recorded in M. vitrata across diverse geographic areas in Africa, India, and Asia limits the potential use of the traps when used as monitoring or mass trapping tools.…”
Section: Discussionsupporting
confidence: 70%
“…There are three putative Maruca species, one in Latin America, one each in Oceania (including Indonesia) and in Asia, Africa, and two putative M. vitrata subspecies in Asia and Africa have also been reported [ 8 ]. A recent study found the presence of different Maruca species and/or subspecies in different continents based on the diversity within pheromone binding protein genes [ 34 ]. Since different species or subspecies appear to exist in the genus Maruca , the pheromone composition and reception of pheromone may not be uniform in different geographical locations.…”
Section: Introductionmentioning
confidence: 99%
“…However, the His70 in the histidine gate is substituted with an Arg in OfurPBP2. In fact, there are several lepidopteran odorant binding proteins (OBPs) that have His70 substituted with either an arginine ( Helicoverpa armigera OBP15 29 and Papilio xuthus GOBP 30 ) or with a lysine ( Maruca vitrata PBP2 31 and Conogethes punctiferalis PBP1) 32 . Furthermore, in OfurPBP2 there is a His88 residue in α5 helix that is not present in the other PBPs 16,23,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, it is reported that the genus Maruca includes several species and/or subspecies that are difficult to distinguish morphologically, and even M. vitrata has long been thought to be a complex of several cryptic species [10]. There are also reports about M. vitrata populations exhibiting a differential response to pheromones in South and Southeast Asia (including India), due to the variability within the pheromone-binding protein genes [11]. So, it is quite possible that M. vitrata populations occurring across varied agro-ecological regions of India are also genetically diverse.…”
Section: Introductionmentioning
confidence: 99%